Estudo comparativo do perfil proteico do fluido intersticial testicular de espécies de valor zootécnico - Melo, Révila Bianca Ferreira de (2017)
The testicular interstitial fluid (FIT) is located in the interstitial region of the testis, which is synthesized by Leydig cells, lymphatic and blood cells and connective tissue. FIT performs several functions, such as: transport of hormones and nutrients to the seminiferous epithelium, transport of spermatozoa and has influence on endocrine and gametogenic functions of the testis. In the constitution of FIT it is possible to find proteins synthesized by several cell types, such as Sertoli cells, Leydig cells and germ cells. The volume and concentration of certain FIT proteins are sensitive to changes in the endocrine hormones and changes in the local testicular environment, thus, the protein constitution of FIT may reflect the status of spermatogenesis. From the information above, the objective of the present work was to build the protein profile of FIT, in addition to performing a comparative analysis of the protein profile with different species that present zootechnical value (bovine, ovine, rabbit and quail). The FIT was collected by percolation and the proteins were precipitated with cold ethanol (4 ° C). Subsequently, the proteins were sepals by one-dimensional electrophoresis with a 4% mesh in the stacking gel and 10% in the running gel. Then, the protein bands obtained on the gel were analyzed through the QuantityOne® program and compared through the unpaired T-test (p <0.05) through Statview®. 263 bands were detected in the triplicate of bovines, 317 proteins in triplicate of TIF geis of sheep, 218 bands in rabbits and 217 bands in TIF of quail. It was observed that there are 9 bands in common with all species and while in the mammals adopted in the study it was observed that there are 10 bands in common, however, the statistical difference in relation to these bands. Comparing the pattern of the gels made with other studies it was observed that TIF proteins have several origins, such as: blood plasma, seminiferous tubules, seminal plasma and others, and that most TIF proteins are synthesized by the Sertoli cells. Leydig and germinating. From the construction of the protein profile, it was observed that the electrophoresis technique is effective for the detection of protein bands. However, it is necessary to identify mass spectrometry to amplify the information about TIF proteins: origin of these proteins and how they can act under the spermatogenesis.